Intelligent emotion and sensory remote prioritisation for patients with multiple chronic diseases - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Intelligent emotion and sensory remote prioritisation for patients with multiple chronic diseases by Alamoodi, Abdullah Hussein